Building Future Leaders: Integrating Soft Skills in Multan’s Secondary Education - Junaid, Muhammad; Bouchra Eloraiby; Zhong Wanjuan (Corresponding Author) (Al-Qanṭara, 2024)
This research study aimed to investigate the integration of soft skills in secondary classrooms in Multan, Pakistan. Four research questions guided the study: teachers' perceptions of soft skill integration's importance, the methods used to integrate soft skills, the difficulties hindering integration, and suggested strategies for improving soft skill development. Data from 386 public and private secondary teachers were collected through questionnaires and interviews, analyzed quantitatively and qualitatively. The study found that soft skills, encompassing cognitive and non-cognitive abilities, are crucial for students' future success. Both public and private school teachers recognized the significance of integrating soft skills in secondary education. Gender and school type showed no significant differences in teacher perceptions. Recommendations for improvement include raising parental awareness of soft skill development and incorporating soft skills training in teacher education. Addressing this issue is essential for preparing students to thrive in their professional careers and adapt to the changing world.